An analysis of code mixing used by carla yules on youtube podcast - Safika Zenda Erly Tasya; Rosita Ambarwati; Yuli Kuswardani (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
The aim of this research focuses on typesof code mixing that used by Carla Yules on YouTube Podcast. The method of this research used qualitative research. The data of this research were taken from Carla Yules Video YouTube Podcast. The researcher used documentation techniques to obtain data. The researcher in analyzing data using “Flow Model” theory of Miles and Huberman. The result of this research, the researcher used Muysken’s theory. The researcher found out three types that appeared in Carla Yules YouTube Podcast. There are Insertion, Alternation, Congruent lexicalization. Insertion has the highest percentage.Congruent lexicalizationhas the lowest percentage.